Study on Willingness to Pay and Impact Mechanism of Gutter Oil Treatment: Taking Urban Residents in Sichuan Province as an Example - Cheng, Peng; Xinyu, Liang; Sidai, Guo; Yubing, Qian (Frontiers in Psychology, 2021)
“Gutter oil” is a term for the practice of recycling used waste oil from restaurant fryers, sinks, and even slaughterhouses and sewers, and has been a major food safety and sanitation issue in China for many years. However, with proper treatment, these issues can be mitigated, turning large amounts of waste product into valuable resources and conserving energy resources. Based on this questionnaire survey conducted in the cities of Chengdu and Mianyang in Sichuan, China, this paper uses the value evaluation method to measure urban residents’ willingness to pay for the treatment of gutter oil, and explores the factors and path influencing residents’ willingness to pay based on the extended theory of planned behavior. The results of this study affirms the validity and universality of the Theory of Planned Behavior. Behavioral attitude, perceived behavioral control, and subjective norms have a direct positive impact on their willingness to pay. Risk perception and past experience indirectly affect residents’ willingness to pay for gutter oil through the intermediary variable of behavioral attitude, which means that the public’s risk awareness can be improved by vigorously publicizing the harmful effects of gutter oil, thereby also increasing acceptance toward gutter oil treatment. As an intermediary variable, subjective norms have a significant indirect effect on the impact path of past experience on willingness to pay, which reflects the significant influence of subjective norms such as reference group and environment. The results show that urban residents have a higher willingness to pay for the treatment of gutter oil. The mean willingness to pay is 7.75 RMB per month per capita.